Progresso genético da soja no Brasil quanto à caracteres fisiológicos e agronômicos - Todeschini, Matheus Henrique (2018)
Soybean (Glycine max L. Merrill) is one of the main crops in a global level, being used in the most diverse fields of agroindustry for being an excellent oil and protein source. Productivity of the crop in Brazil has increased considerably in the last decades, from 1748 kg ha-1 in the 1970s, to 3362 kg ha-1 in the 2016/17 crop season. In this sense, genetic progress researches of agronomic and physiological characters are of great value, since they can indicate new directions for the feature improvement of the culture. The objective of this study was to identify the genetic progress in agronomic and physiological characteristics of soybean in a historical series of cultivars released for cultivation in south Brazil. There were 29 soybean cultivars evaluated, which were released between years of 1965 to 2011. The experiments were conducted in Realeza – PR and Pato Branco – PR, in 2016/17 crop season. The used experimental design was the random block design with three replications. The experimental units were constructed with four lines of five meters long spaced in 0,5 m between lines, using 35 seeds m-2. Cultural practices were carried out in accordance with the technical recommendations for the culture. The results showed genetic gain of 39,42 kg ha-1 year-1 in the locals average. The moderns cultivars present higher values of biological yield (BY), harvest index (HI), number of pods per plant (NPP), and height of the bottom pod (HBP), in addition to presenting lower number of branches per plant (NBP), plant height (PH), and lodging score (LS). There was a reduction in the vegetative period of the modern cultivars, causing the relationship between the reproductive and vegetative (R/V) to be increased. Genetic progress was also observed for photosynthetic rate (Pn – r= 0,67**) and transpiration rate (Tr – r= 0,88**). However, for the traits of water use efficiency (WUE) and stomatal conductance (gs), no significant differences were found. Among the evaluated traits, BY, NPP, HI, R/V, and number of grains per pod (NGP) presented the highest associations with grain yield (GY), besides the physiological characters Pn, Tr, and indices of chlorophyll a and b (ICF a and b, respectively). Therefore, breeding strategies that maximize the R/V ratio, and also prioritize indirect selection through the HI, BY, and NPP traits, as well as the physiological ones of Pn, Tr, and ICF a and b, may contribute to increased genetic progress of the culture in the coming years.